A Religiously-tailored, Multilevel Intervention in African American Churches to Increase HIV Testing: Rationale and Design of the Taking It to the Pews Cluster Randomized Trial - Berkley-Patton, J. (Contemp Clin Trials, 2019)
HIV continues to disproportionately impact African American (AA) communities. Due to delayed HIV diagnosis, AAs tend to enter HIV treatment at advanced stages. There is great need for increased access to regular HIV testing and linkage to care (LTC) services for AAs. AA faith institutions are highly influential and have potential to increase the reach of HIV testing in AA communities. However, well-controlled full-scale trials have not been conducted in the AA church context. We describe the rationale and design of a 2-arm cluster randomized trial to test a religiously-tailored HIV testing intervention (Taking It to the Pews [TIPS]) against a standard information arm on HIV testing rates among AA church members and community members they serve. Using a community-engaged approach, TIPS intervention components are delivered by trained church leaders via existing multilevel church outlets using religiously-tailored HIV Tool Kit materials/activities (e.g., sermons, responsive readings, video/print testimonials, HIV educational games, text messages) to encourage testing. Church-based HIV testing events and LTC services are conducted by health agency partners. Control churches receive standard HIV education information. Secondarily, HIV risk/protective behaviors and process measures on feasibility, fidelity, and dose/exposure are assessed. This novel study is the first to fully test an HIV testing intervention in AA churches – a setting with great reach and influence in AA communities. It could provide a faith-community engagement model for delivering scalable, wide-reaching HIV prevention interventions by supporting AA faith leaders with religiously-appropriate HIV toolkits and health agency partners.